PRAKTEK MAWAH MELALUI MUDHARABAH DALAM MASYARAKAT ACEH - ABDURRAHMAN ABDURRAHMAN (PREMISE LAW JURNAL, 2015)
Mawah of Mudharabah is a Syariah-based economic system in Aceh. It has been developed and practiced by the Aceh community since the 16th century long before Indonesian dependence. The problems answered in this study were how Mudharabah/Mawah practice was implemented in Ingin Jaya Subdistrict, Aceh Besar District, how Mawah law in Islam is, how Mawah problem was solved when a dispute occurred in Ingin Jaya. Ta’awun (assisting) theory and ‘Urf theory, Justice theory and Mashlahat theory were the related theories used in this study. By using an empirical juridicial approach the study was conducted by meeting the study respondents and informants to interview them directly. The study found that the practice of Mawah is in accordance with the practice of Syariah Islam so called Mudharabah, a practice which is legally based on Al-Quran and Hadits. The study suggested to improve and sustain Mawah activity as it is very useful in helping the community livelihood. Keywords: Mawah, Mudharabah, Aceh